Role of S6K1 in regulating self-renewal of hematopoietic stem cells and propagatoin of leukemia - Ghosh, Joydeep (2016)
Indiana University-Purdue University Indianapolis (IUPUI) === The development and function of hematopoietic stem cells (HSCs) is regulated by numerous signaling pathways including Akt-mechanistic target of rapamycin complex1 (mTORC1) pathway. Dysregulation of this pathway results in impaired HSC function and contributes to the development of hematologic malignancies. Activated mTORC1 phosphorylates and subsequently activates ribosomal protein S6 kinase 1 (S6K1). To study the role of S6K1 in hematopoiesis as well as leukemogenesis, we used a genetic model of S6K1 deficient mice (S6K1-/-). We found that loss of S6K1 expression in HSCs results in reduction of absolute HSC number in bone marrow (BM). Following chemotherapy, cycling HSCs undergo apoptosis and quiescent HSCs are required to cycle to regenerate the hematopoietic system. S6K1 regulates the quiescence of HSCs and in the absence of S6K1, mice are more susceptible to repeated myeloablative stress. We also observed that loss of expression as well as gain of expression of S6K1 affects the self-renewal ability of HSCs. Interestingly, when we overexpressed S6K1, it also resulted in reduced self-renewal of HSCs. Next, we assessed the role of S6K1 in the propagation of acute myeloid leukemia (AML). The mixed-lineage leukemia (MLL) gene is required for the maintenance of adult HSCs. Translocations in MLL are detected in approximately 5-10% of adult acute leukemia patients and in approximately 70% of acute leukemias in infants. We expressed MLL-AF9 fusion oncoprotein in WT and S6K1-/- hematopoietic stem and progenitor cells (HSC/Ps) and performed serial transplantation. Upon secondary transplantation, recipients of S6K1 deficient AML cells survived significantly longer compared to controls. In vitro, pharmacological inhibition of S6K1 activity resulted in reduced growth of primary human cells expressing MLL-AF9. Both human and murine HSC/Ps expressing MLL-AF9 showed reduced mTORC1 activity upon inhibition of S6K1 suggesting that loss of S6K1 activity results in reduced Akt-mTORC1 activation both upstream and downstream of mTORC1. Overall, our studies establish a critical role of S6K1 activity in the maintenance of HSC function and in the propagation of leukemia.